PEMANFAATAN TITHONIA DAN AZOLLA UNTUK MENINGKATKAN HASIL JAGUNG MANIS ORGANIK - Krisnarini Krisnarini (STIPER Dharma Wacana Metro, 2014)
The utilization of tithonia and azolla in increasing organic sweet corn products (Krisnarini). Tithonia treatment gives as good sweet corn products as the control, while 3,5 ton.ha-1 and 7 ton.ha-1azolla treatment give the same good result but they are better than the control one which is supported by the height of the plant, dried mass of the plant and corn mass per cop variable but there is no interaction between both of the treatment.Keywords: Tithonia, Azolla, Sweet Corn.